2017
DOI: 10.22146/gamaijb.12541
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Incidence of Interfirm Collaboration: Evidence from Research and Development Companies in Malaysia

Abstract: Nowadays, interfirm collaboration has become an increasingly popular strategy among many organizations in various industries, in order to remain competitive. Based on the contingency theory, this paper examines the moderating effect of interfirm collaboration on the relationship between Human Resource Management (HRM) practices and organizational performance. Interfirm collaboration refers to the collaboration strategies undertaken by R&D companies, with other companies in similar or diverse functional areas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…At present, based on the findings there seems to be limited information on the success and failure of CM, particularly within the context of the tool and die industry in Malaysia with no significant research or initiative identified. Even after considering the current scientific literature related to collaborative initiative such as from (Adnan et al, 2017), we were unable to determine the level of its success or failure in Malaysia. However, understanding the factors that contribute towards the success or failure of CM in practice is the key to devise a better strategy for effective implementation (Rana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…At present, based on the findings there seems to be limited information on the success and failure of CM, particularly within the context of the tool and die industry in Malaysia with no significant research or initiative identified. Even after considering the current scientific literature related to collaborative initiative such as from (Adnan et al, 2017), we were unable to determine the level of its success or failure in Malaysia. However, understanding the factors that contribute towards the success or failure of CM in practice is the key to devise a better strategy for effective implementation (Rana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Collaboration is important in developing new products (Adnan et al, 2017). In order to develop and commercialize new products, collaboration in a network of companies and institutions is important for gaining access to marketing expertise, production facilities, operational knowledge and funds (Adnan et al, 2017). Working together also has its challenges.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%